Danos do percevejo-barriga-verde dichelops melacanthus (dallas, 1851) (hemiptera: pentatomidae) na cultura do milho - Rodrigues, Rodrigo Borkowski (2011)
The research objective was to evaluate the damage caused by D. melacanthus in the initial phase of the maize crop. Two field trials were conducted in Rondonópolis, Mato Grosso, and two greenhouse trials occurred in Santa Maria, Rio Grande do Sul. In all experiments artificial infestation of cages was done using laboratory reared stink bugs. In all experiments the experimental design adopted was randomized blocks. In the field trials, the experimental units were 1m x 1m x 1m cages with six corn plants each. One of the trials evaluated the combinations of population levels and coexistence periods of green belly stink bugs adults with the crop and the other one aimed to estimate the economic threshold level of D. melacanthus in corn. In both trials 21 days after emergence (DAE), the number of plants damage by stink bugs (PD) and the plant height were evaluated. The plants height were measured at harvesting, the shoot of dry mass(SDM)was determined , as well as the number of ears per plot (EN), the number of rows per ear (RE), number of kernels per row (KR), the 1,000-grain weight (TGW) and the grain production. In addition a greenhouse trial was done to evaluate the effect of seed treatment with insecticide thiamethoxan on the injuries to maize in the initial phase caused by D. melacanthus. The other trial aimed to compare the damage caused by nymphs and adults D. melacanthus in the initial phase of corn plants. In both experiments the height and dry mass accumulation of roots and shoots were measured. The obtained data was submited to variance analysis, regression tests or mean comparation besides the estimation of the Pearson correlation coefficients for the evaluated characters. The stink bugs damages in the initial phase were reflected at the end of the cycle in most of evaluated characters. The losses were greater when the coexistence period occurred just after the crop emergence, rising with the increase of the coexistence period and the density levels. High correlation was found between height at 21 DAE with SDM, grain production and yield components (EN, RE and KR). The number of ears per plot was the most affected character by the stink bugs attack. The economic threshold level obtained of D. melacanthus in maize was 0.50 stink bugs per m2. The seed treatment with thiamethoxan reduced the damage caused by the stink bugs and provided normal development of plants even when subjected to higher population levels of stink bugs. Four nymphs of D. melacanthus cause injury to corn in initial phase at intensities similar to those caused by an adult.